Message from the Organizing Committee and Plenary Presenter - Rátgéber, László (Sport- és Egészségtudományi füzetek, 2026)
The National Basketball Academy in Pécs proudly hosted the 6th International Basketball Conference, maintaining the same high standards as before, with world-class international experts sharing their knowledge with attendees. Over the past three years, these conferences have compiled a complete university-level curriculum.